Rondas infantiles como estrategia en el desarrollo de las habilidades motrices en los niños y niñas de Educación Inicial de la Unidad Educativa Adolfo María Astudillo - García Altamirano, Carmen Karina (2022)
In the present research work, the theme "Children's Rounds as a strategy in the development of motor skills in children of initial education, of the Adolfo María Astudillo educational unit" is carried out, which is of vital importance with the purpose of provide the necessary information to guarantee that the objectives are met, especially the general one, which is to analyze the importance of children's rounds as a strategy in the development of motor skills in children of initial education of the Adolfo María Astudillo Educational Unit, province from the rivers. Likewise, the descriptive type of research was carried out since through this a correct analysis and synthesis of the information that was used in the development of this work was inquired and carried out, a study sample was also obtained in which A survey was used where great results were achieved based on obtaining the necessary knowledge from parents and teachers of the aforementioned educational unit, which allowed us to conclude that the practice of children's rounds does help improve the development of motor skills.